The effect of marine parameters on salinity via statistical approaches - Mohamad Hamzah, F.; Mohammed, S.N.S.; Syed Abdullah, S.M.; Abdul Maulud, K.N.; Mohd Razali, S.F.; Kamarudin, M.K.A. (2020)
The purpose of this study was to identify the relationships between water quality parameters of marine water and to determine parameters that affect much on salinity of surface water. This is a quantitative study which focusses on modelling of salinity on three marine parameters (temperature, dissolved oxygen and conductivity) from six monitoring stations in the Straits of Johor, Malaysia. Pearson correlation indicates the occurrence of significant linear relationship between salinity and conductivity for each station. The regression model of salinity shows some significant effects of a few marine parameters. A significant correlation of about 0.8 between salinity and conductivity for all stations shows that their relationship is moderately high as compared to temperature and dissolved oxygen. The fitted models indicate that similar ecological conditions can be observed at one of the monitoring stations for each Western and Eastern parts of the Straits of Johor as the salinity is dominantly influenced by the changes in temperature, dissolved oxygen and conductivity.